Decentralisation processes in Montenegrin public administration - Radević, Ivan (Lex localis, 2019)
The paper aims to assess the organisational design of the public health care system of Montenegro from the organisational and legal standpoint, and in particular from the position of a likelihood for the system decentralisation through an inclusion of local self-governments with the goal to increase the quality of health care. The qualitative analysis is based on the method of case study. The research covers the analysis of Montenegrin legislation, and in particular Montenegrin and European regulations and strategic documents that refer to local self-governments and health care system. Individual and group interviews were conducted with top executives in the Ministry of Health of Montenegro, Health Insurance Fund of Montenegro and Ministry of Public Administration. The research shows that Montenegrin health system is predominantly centralised, and lacks substantial involvement by local self-government in health care related services. The need for a stronger participation of municipalities (and private entities) is indicated, for the purpose of achieving a stronger level of quality of the health care services.
Keywords: Decentralizacija; Decentralization; Javne službe; Local self-government; Lokalna samouprava; Medical care; Public services; Zdravstveno varstvo